Seketeng Tourism Resilience: Revealing the Social Capital of the Community of Kampung Lawang Seketeng in Breaking Tourist Attraction Based on Strategic Action Planning - Yuni Setyaningsih; Shafa Alya Nur Faizah; Muhammad Faiz Marhaditya (Jurnal Indonesia Sosial Sains, 2024)
Tourism plays a crucial role in regional economic development, yet many historical sites, including Kampung Lawang Seketeng, remain underutilized. Despite its rich historical and cultural heritage, this area has not attracted sufficient tourist attention. The main challenges include a lack of promotion, inadequate infrastructure, and low community awareness of its historical value. This research aims to explore the social capital of Kampung Lawang Seketeng’s community and its potential in enhancing tourist attraction through Strategic Action Planning. Using a qualitative phenomenological approach, data were collected through in-depth interviews and observations, supplemented by literature review. Results indicate that strengthening community involvement, improving promotional strategies, and enhancing infrastructure could significantly boost tourism. The study contributes to heritage tourism development by offering a strategy that aligns with local social dynamics, potentially increasing tourism and improving the local economy. Future implementation of these strategies requires collaborative efforts from local government, stakeholders, and the community.